STRENGTHENING THE PROFILE OF PANCASILA STUDENTS THROUGH INTEGRATION OF MADURA COASTAL LOCAL WISDOM IN NATURAL AND SOCIAL SCIENCE LEARNING IN PRIMARY SCHOOL - Pritasari, Ade Cyntia; Jannah, Ana Naimatul; Tarika, Siti; Rafiyanzah, Rafiyanzah (International Conference on Humanity Education and Society (ICHES), 2024)
Students in Indonesia are expected to be able to participate in sustainable global development and be resilient in facing various challenges. Efforts to prepare students to face the future are to equip them to become lifelong learners with global competence, character and behavior according to the values of Pancasila. The aim of this research is to analyze the local wisdom of the Madura coast and the dimensions of the Pancasila student profile contained in this local wisdom as well as the form of integration of Madura coast local wisdom in natural and social science learning in primary schools. This research uses a qualitative approach with a descriptive type. This research uses descriptive qualitative research to explore local coastal wisdom and its integration in strengthening the profile of Pancasila students. Data collection techniques used include interviews and documentation. The research results show that: 1) The local wisdom of the Madura coast includes the local wisdom of fisherman in the form of rokat tase’; and bagan apung; as well as the local wisdom of salt farmers in the form of Madurese salting techniques and nyadar; 2) Local wisdom of the Madura coast can be integrated into natural and social science learning in primary schools; 3) The dimensions of the Pancasila student profile contained in the local wisdom of the Madura coast include having faith, being devoted to God Almighty, and having noble morals; mutual cooperation; critical reasoning; and creative.